Seven indicators variations for multiple PV array configurations under partial shading and faulty PV conditions. (December 2017) - Dhimish, Mahmoud; Holmes, Violeta; Mehrdadi, Bruce; Dales, Mark; Chong, Benjamin; Zhang, Li
Abstract: The goal of this paper is to model, compare and analyze the performance of multiple photovoltaic (PV) array configurations under various partial shading and faulty PV conditions. For this purpose, a multiple PV array configurations including series (S), parallel (P), series-parallel (SP), total-cross-tied (TCT) and bridge-linked (BL) are carried out under several partial shading conditions such as, increase or decrease in the partial shading on a row of PV modules and increase or decrease in the partial shading on a column of PV modules. Additionally, in order to test the performance of each PV configuration under faulty PV conditions, from 1 to 6 Faulty PV modules have been disconnected in each PV array configuration. Several indicators such as short circuit current (Isc ), current at maximum power point (Impp ), open circuit voltage (Voc ), voltage at maximum power point (Vmpp ), series resistance (Rs ), fill factor (FF) and thermal voltage (Vte ) have been used to compare the obtained results from each partial shading and PV faulty condition applied to the PV system. MATLAB/Simulink software is used to perform the simulation and the analysis for each examined PV array configuration. Highlights: Analysis of multiple Photovoltaic (PV) array configurations such as S, P, SP, TCT and HC. Seven Indicators including Isc, Impp, Voc, Vmpp, Rs, FF and Vte have been examined. New mathematical calculations for estimating the series resistance is proposed. The examined PV array configurations are modelled using MATLAB/Simulink software.